2021
DOI: 10.1088/1755-1315/753/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Geometry aspect review of the natural circulation system as innovation in passive cooling of nuclear reactor

Abstract: The passive nuclear reactor cooling system has become a fascinating topic, especially since the nuclear incident in Fukushima Daiichi, Japan. This study proposed to review a natural circulation-based passive cooling system in the geometry aspects of the loop. The numerical review was carried out using COMSOL Multiphysics software to study the geometry effect on the loop’s fluid characteristics. Moreover, related research data to the study of the effect of fluid flow rate on one of the advanced nuclear reactors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Then, the authors' work has been done on paper [9], demonstrated experimentally that expansion tank placement is crucial in single-phase NCLs. Also, subsequent work by experimental and modelling showed that loop geometry could affect natural circulation-based cooling systems [9][10][11][12]. These studies revealed that the instability of the NCL is influenced by the loop geometry.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Then, the authors' work has been done on paper [9], demonstrated experimentally that expansion tank placement is crucial in single-phase NCLs. Also, subsequent work by experimental and modelling showed that loop geometry could affect natural circulation-based cooling systems [9][10][11][12]. These studies revealed that the instability of the NCL is influenced by the loop geometry.…”
Section: Introductionmentioning
confidence: 95%
“…The effect of coolant temperature variations on NCL instability was analysed in paper [19] using the commercial code Fluent 6.3. Also, the authors have modelled the effect of the natural circulation loop geometry using the COMSOL Multiphysics software [10,11]. Motivated from the above description, in this paper, we studied the transient and steady-state of the natural circulation system in the molten salt loop with vertical heater and horizontal cooler using computational fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%